Fostering hearts - Lim, Andrea Jia Min (Nanyang Technological University, 2024)
Fostering Hearts is a communications campaign aimed at spreading awareness about foster care amongst young adults (aged 21-35) in Singapore. It aims to enable keen young adults with ways to make a difference in the lives of foster children and take steps towards becoming foster parents in the future. Children in need of fostering in Singapore have experienced abuse, neglect, or family-related challenges. With the number of child abuse cases rising in recent years, foster parent recruitment remains critical for providing children in need with sustenance, shelter, clothing, and emotional care (MSF, n.d.). However, a significant proportion of young adults aged 21-35 lack an understanding of the fostering scheme in Singapore. The Fostering Hearts team identified the importance of sowing the seeds of awareness in young adults early to allow individuals ample time to ponder and understand the complexities of fostering – a decision that sometimes takes years to finalise. The campaign aimed to enhance awareness of fostering-related issues, cultivate positive attitudes towards fostering in Singapore, and ultimately encourage behaviours that translate to an increase in intention to foster. Campaign strategies included increasing understanding of the foster care landscape through videos from various points of view, exploring fresh interactive methods of storytelling such as through developing an online game, and producing an informative guide to fostering that enables keen young adults to take actions to support the cause. This paper details the research undertaken, campaign activities executed, and evaluates the campaign’s effectiveness, longevity, and limitations, and provides recommendations for future campaigns.